Moral Wajib Pajak, Sanksi Pajak, Dan Kebijakan Pengampunan Pajak Terhadap Kepatuhan Pajak Wajib Pajak Orang Pribadi (Studi Empiris Di Kantor Pelayanan Pajak Pratama Jayapura) - Dwi Bagus Saputra Jaya; Meinarni Asnawi; Cornelia D. Matani (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2023)
This study aims to provide empirical evidence of the effect of taxpayer morale, tax sanctions, and tax amnesty policies on individual taxpayer compliance in the city of Jayapura. This study uses control variables consisting of gender, age, education, occupation, as well as income level and NPWP ownership. This research was conducted using a survey method by distributing online questionnaires due to the COVID-19 outbreak of the Omicron variant in Indonesia and globally, distributed to 100 respondents with a population of 3.274individual taxpayers. The data analysis method used is the Structure Equation Model (SEM) approach with the Partial Least Square (PLS) method. The sampling method used is a snowball sampling technique, which is a sampling technique used to obtain samples with a rolling process from one respondent to another.Based on the examination of the results of this study, the morale of taxpayers and tax amnesty policies affect individual taxpayers' tax compliance, while tax sanctions have no effect on individual taxpayers' tax compliance in the city of Jayapura.